FAKTOR EKSTERNAL DAN INTERNAL YANG MEMPENGARUHI PEMBIAYAAN BANK UMUM SYARIAH KEPADA UMKM - Asfi Manzilati; Mega Ria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze the influence of external factors (inflation, BI rate, exchange rate) and internal factors (CAR, ROA, NPF, FDR, TPF and BOPO) on the financing disbursed by Islamic commercial banks to MSMEs. The data used in this study is monthly data from January 2015 to December 2021 sourced from the official website of The Indonesian Financial Services Authority, the Central bank of Indonesia, the Ministry of Trade of the Republic of Indonesia, and the Central Bureau of Statistics. The methodology used in this study is the Error Correction Model (ECM), using Eviews 10 as an estimation tool. The results of this study indicate that in the short term, all variables have an insignificant effect on the financing disbursed by Islamic commercial banks to MSMEs. For the long-term, the inflation variable, FDR, and NPF have positively and significantly affected financing disbursed by Islamic commercial banks to MSMEs. In contrast, the BOPO variable negatively affects financing disbursed by Islamic commercial banks to MSMEs. Other variables, namely the BI rate, exchange rate, CAR, ROA, and NPF, have an insignificant effect on the financing disbursed by Islamic commercial banks to MSMEs.